Effects of fasting and nutritional restriction on the isotopic ratios of nitrogen and carbon: a meta‐analysis. Issue 21 (8th October 2015) - Hertz, Eric; Trudel, Marc; Cox, Marlin K.; Mazumder, Asit
Abstract: Many organisms experience fasting in their life time, and this physiological process has the potential to alter stable isotope values of organisms, and confound interpretation of food web studies. However, previous studies on the effects of fasting and starvation on stable isotopes show disparate results, and have never been quantitatively synthesized. We performed a laboratory experiment and meta‐analysis to determine how stable isotopes of δ 15 N and δ 13 C change with fasting, and we tested whether moderators such as taxa and tissue explain residual variation. We collected literature data from a wide variety of taxa and tissues. We surveyed over 2000 papers, and of these, 26 met our selection criteria, resulting in 51 data points for δ 15 N, and 43 data points for δ 13 C. We determine that fasting causes an average increase in the isotopic value of organisms of 0.5‰ for δ 15 N and that the only significant moderator is tissue type. We find that the overall effect size for δ 13 C is not significant, but when the significant moderator of tissue is considered, significant increases in blood and whole organisms are seen with fasting. Our results show that across tissues and taxa, the nutritional status of an organism must be considered when interpreting stable isotope data, as fasting can cause large differences in stable isotope values that would be otherwise attributed to other factors. Abstract : A laboratory experiment and meta‐analysis were performed to determine how fasting influences estimates of stable isotopes. We found that the only supported moderator was tissue type, and we found significant increases in stable isotopes of nitrogen with fasting that are approximately one‐seventh of a trophic level.